A Teacher's Guide to Using a Multiple Schedule of Reinforcement in Educational Settings. (September 2020) - Vargo, Kristina K.
Classroom teachers are responsible for providing high-quality instruction to multiple students simultaneously. When students engage in problem behaviors, instructional quality and instructional time may be negatively impacted. A multiple schedule of reinforcement is a behavioral intervention strategy that allows teachers to signal to students specific contexts under which behaviors will be reinforced (and also not reinforced). This article defines and describes a multiple schedule of reinforcement, its utility in educational settings, and recommendations for effective implementation.